Accounting : The Basis for Business Decisions - Meigs, Robert F. and Meigs. Walter B. (New York McGraw-Hill, 1993)
This edition includes an increase in real-world examples, greater focus on the uses of accounting information and updated material to reflect contemporary accounting practices. Features include comprehensive problems which tie together concepts presented over a span of chapters
Include Appendix and Index
Keywords: Accounting